P050: Electronic health record perceptions and utilization by physicians in urban emergency departments. (2nd June 2016) - Graham, T.A.; Ballermann, M.; Lang, E.; Bullard, M.; Parsons, D.; Mercuur, L.; San Augustin, P.; Ali, S.
Abstract : Introduction: In 2006, Alberta implemented an Electronic Health Record called the Alberta Netcare Portal (ANP). The ANP provides provincial read-only access to lab tests, diagnostic imaging, medication information and numerous text reports. There is no computerized order entry, and care is coordinated using a hybrid of paper charting and various electronic systems. Here, we quantify observed ANP use by physician participants providing care in four urban Emergency Departments (EDs) in Alberta. The results form part of a larger mixed methods research project aimed at detecting broader implications of ANP use for patient care.Methods: Between October 2014 and July 2015, ED physicians at four EDs (University of Alberta Hospital [UAH], Grey Nuns Community Hospital [GNCH], Foothills Medical Centre [FMC], Peter Lougheed Centre [PLC]) participated in structured clinical observations. Observations were purposively sampled during the first hours of shifts, when physicians orient themselves to the patients they will see during the rest of their shift, including reviewing available historic patient information. Observers used a tablet based tool to generate a time-stamped record of the information tools used alongside patient care. Information tools included permanent paper records, paper excluding permanent documentation, the ANP, clinical and other applications accessed via desktop computers, and mobile devices. Observers also recorded contextual data, including participant commentary, on paper field notes.Results: Across the 4 sites, 142 physicians participated in 376 sessions for a total of 566 observed physician-hours. Participants accessed information in different computerized applications and on paper (i.e., a 'hybrid' care environment). The highest proportion of observed physician time interacting with ANP was observed at the UAH (7.0%-8.1%, all values 95% Confidence Intervals). Physicians spent less time using ANP at GNCH (4.1%-4.8%), which was similar to the Calgary EDs (FMC: 4.4-5.3% and PLC: 5.2%-5.9%). Thematic analysis of field notes showed that ANP acceptance was very high. Patient safety concerns were recorded related to care provided alongside 'hybrid' patient records.Conclusion: We found high physician acceptance of ANP based on documented comments and observed usage. We posit a high potential for EHRs such as ANP to support improved care coordination which remains partly realized.